The Role of Social Media in Introducing Budo Tourism Village, North Sulawesi Province - Alma Karangan Pongtuluran; Margaretha N. Warokka; Andih, Deisy Ch. (Jurnal Internasional Riset Bisnis Pariwisata, 2024)
Budo Village is one of the tourist villages located in the North Minahasa district, North Sulawesi Province. This village was included in the top fifty categories of the 2022 tourism village award, and received the best category in digital content creator, so it went viral and became the subject of discussion in Manado. From observations and some visitor statements, they know this village through social media. is it true that social media has played a role in introducing this village to the virtual world? The purpose of this research is to analyse the role of social media in introducing Budo Village as a tourist destination. The research approach is descriptive, by conducting a survey, distributing questionnaires to 150 respondents determined by a purposive sampling technique. The data collected was then analysed using percentages. The results showed that social media platforms such as Facebook and YouTube have played a role in introducing Budo Village as a tourist destination. To maintain the popularity of Budo Village, the manager must open access to other social media platforms. In addition, it is necessary to diversify tourist attractions so that there are more creative posts, which is believed that the popularity of this destination will be maintained, and will have an impact on the number of tourist visits to these tourist sites.